Bioresorbable vascular scaffold implantation in acute coronary syndromes: clinical evidence, tips and tricks - Giacchi, Giuseppe; Ortega-Paz, Luis; Brugaletta, Salvatore; Ishida, Kohki; Sabaté, Manel (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Percutaneous coronary intervention (PCI) with a drug-eluting stent (DES) is routine treatment for patients with acute coronary syndromes (ACS). However, permanent metallic caging of the vessel has several shortcomings, such as side branch jailing and impossibility of late lumen enlargement. Moreover, DES PCI is affected by vasomotion impairment. In ACS a high thrombus burden and vasospasm lead to a higher risk of acute and late acquired stent malapposition than in stable patients. This increases the risk of acute, late and very late stent thrombosis. In this challenging clinical setting, the implantation of bioresorbable vascular scaffolds (BVS) could represent an appealing therapeutic option. Temporary vessel scaffolding has proved to have several advantages over metallic stent delivery, such as framework reabsorption, late lumen enlargement, side branch patency, and recovery of physiological reactivity to vasoactive stimuli. In the thrombotic environment of ACS, BVS implantation has the benefit of capping the thrombus and the vulnerable plaque. Bioresorbable vascular scaffolds also seems to reduce the incidence of angina during follow-up. Acute coronary syndromes patients may therefore benefit more from temporary polymeric caging than from permanent stent platform implantation. The aim of this review is to update the available knowledge concerning the use of BVS in ACS patients, by analyzing the potential pitfalls in this challenging clinical setting and presenting tricks to overcome these limitations.